An Analysis of Code Mixing used in Daniel Mananta Video YouTube Channel - Fenty Debora Napitupulu; Lastri Wahyuni Manurung (Merwinspy Publisher, 2023)
Code mixing is a phenomenon of mixing one language code with another language code that is used simultaneously by people tocommunicate differently and sometimes can change the speaker to another language but with the same pronunciation of the meaning. The objectives of this research to find out the types of code mixing and the factors influencing code mixing usage in Daniel Mananta Video YouTube Channel. The research designed this study with qualitative method with the data from transcript of Daniel Mananta Video YouTube Channel. The findings show that: there are the type of code namely intra-sentential, intra-lexical and involves changes in pronunciation. There are also several factors that influence code mixing such as talking about a particular topic and interjection code mixing